2001
DOI: 10.1002/ijc.1403
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of MGMT is associated with protein loss in gastric carcinoma

Abstract: Key words: DNA methylation, gastric carcinoma, MGMTN-methyl-NЈ-nitro-N-nitrosoguanidine (MNNG) and N-methyl-N-nitrosourea (MNU) have been shown to induce gastric carcinoma at a high frequency in rats and mice when given in their drinking water. 1,2 MNNG and MNU produce O 6 -methylguanine, which mispairs with thymine during replication, resulting in conversion of a guanine-cytosine pair to an adenine-thymine pair if the adduct is not removed. 3,4 The O 6 -methylguanine-DNA methyltransferase, MGMT, is a DNA repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 20 publications
4
65
1
Order By: Relevance
“…In the present study, promoter methylation was detected in 14.1% of gastric carcinomas and a loss of MGMT expression was found in 11.4 -13.3% of tumours. Our result is lower than those of Oue et al (2001) or Park et al (2001) but is similar to those of Esteller et al (2001a). The study by Park et al (2001) showed that there was no significant difference in the protein expression between cases with MGMT methylated and unmethylated tumours.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, promoter methylation was detected in 14.1% of gastric carcinomas and a loss of MGMT expression was found in 11.4 -13.3% of tumours. Our result is lower than those of Oue et al (2001) or Park et al (2001) but is similar to those of Esteller et al (2001a). The study by Park et al (2001) showed that there was no significant difference in the protein expression between cases with MGMT methylated and unmethylated tumours.…”
Section: Discussionsupporting
confidence: 90%
“…The study by Park et al (2001) showed that there was no significant difference in the protein expression between cases with MGMT methylated and unmethylated tumours. But in our results, as well as the study by Oue et al (2001), there were significant differences associated between the loss of MGMT protein expression and promoter methylation (P50.001).…”
Section: Discussionsupporting
confidence: 53%
“…22 In brief, each target sequence was amplified in a 20 L reaction volume containing 10 -20 ng of genomic DNA, 0.2 M 2Јde-oxynucleoside-SЈtriphosphate, 10 mM Tris-HCl (pH 8.3), 50 mM potassium chloride, 2 mM MgCl2, 0.3 M of each primer, and 0.75 units (U) of Ampli Taq Gold (Perkin-Elmer, Norwalk, CT). PCR amplification consisted of 35 cycles of 94°C for 30 seconds, 60°C or 55°C for 30 seconds, and 72°C for 30 seconds, after the initial activation step of 94°C for 10 minutes.…”
Section: P53 Mutation Analysismentioning
confidence: 99%
“…16,[21][22][23][24][25][26][27] Inactivation of the hMLH1 gene by hypermethylation is associated with microsatellite instability in GC. 21 MGMT is a DNA repair gene that removes mutagenic and cytotoxic adducts from the O 6 position of guanine induced by alkylating agents such as MNNG and MNU.…”
mentioning
confidence: 99%
“…Although several reports have been published about methylation of various genes in gastric carcinoma, [5][6][7][8][9][10][11][12][13][14][15] in most of these studies, the methylation status was investigated for just a single gene and no reports have described an association between DNA methylation pattern and CIMP status or histological classification. Kang et al 16) studied DNA methylation of multiple genes and reported that EpsteinBarr virus (EBV)-positive gastric carcinoma frequently shows aberrant methylation; however, they did not investigate whether any association exists between DNA hypermethylation and CIMP status or histological classification.…”
Section: Ink4amentioning
confidence: 99%